LAVEA: Latency-Aware Video Analytics on Edge Computing Platform - Shanhe Yi; Zijiang Hao; Qingyang Zhang; Quan Zhang; Weisong Shi; Qun Li (Proceedings of the International Conference on Distributed Computing Systems, 2017)
We present LAVEA, a system built for edge computing, which offloads computation tasks between clients and edge nodes, collaborates nearby edge nodes, to provide low-latency video analytics at places closer to the users. We have utilized an edge-first design to minimize the response time, and compared various task placement schemes tailed for inter-edge collaboration. Our results reveal that the client-edge configuration has task speedup against local or client-cloud configurations.